Analysis of filtration properties of locally sourced base oil for the formulation of oil based drilling fluids (2014)
Oil based drilling fluids are mixtures of clays, oil and oilier chemical additives suspended or dissolved such as solids and polymers . The environmental problems associated with oil-based drilling fluids are among the major concerns in the petroleum industry leading to increasing stringent regulations to ensure its environmental friendliness. This study examines the use of locally sourced oil like, groundnut oil, melon oil, vegetable oil, soya oil and palm oil as substitute for diesel oil in formulating oil base drilling fluids relative to filtration properties. The filtrate volumes of each of the oils were obtained for filtration control analysis. With increasing potash and industrial starch quantities during formulation of the local oils had their filtration properties (filtrate volume and mud cuke duckness) tending towards that of diesel oil at ambient temperature and atmospheric pressure. When temperature was increased to 70°C and above, the filtration abilities of all the local oil reduced and degraded due to the flocculation of the clay suspension. The drilling fluids formulated -with the local oil where restored by me addition of thinner and organic polymer which significantly stabilized the clay suspension. The polymer and the thinner clearly improved the filtration properties of the locally formulated oil based drilling fluids even when subjected at high temperature, The ranking from the results showing the order of better and effective filtration properties for the local oils are as shown; Melon Oil; Vegetable Oil; Groundnut Oil; Soya Bean Oil and Palm oil.